Disaster Risk Reduction—Japanese Initiatives in the World Agenda. (2nd January 2017) - Kaji, Misako
Abstract : Third United Nations World Conference on Disaster Risk Reduction was held in Sendai, Japan in March 2015, four years after the Great East Japan Earthquake struck on March 11, 2011. Attended by some 150, 000 participants from around the world, the Conference adopted the Sendai Declaration and the Sendai Framework for Disaster Risk Reduction 2015–2030, the latter of which was the successor document to Hyogo Framework for Action. Besides significance in efforts to prevent and mitigate disasters, the successful formulation and adoption of the Sendai Framework served to promote collaboration on UN and other conferences held later that year. Disaster Risk Reduction principles of reducing vulnerabilities and enhancing resilience are especially necessary in the Asia-Pacific region which is over-represented in natural disasters. In December 2015, efforts by Japan and 141 other co-sponsors resulted in a UN Resolution to designate the 5th of November "World Tsunami Awareness Day."